Analysis of the aerobic/anaerobic performance in functionally disabled swimmers: Low classes vs high classes - de Aymerich, J.; de Aymerich, J.; Benavent, J.; Tella, V.; Colado, J. C.; Gonzalez, L. M.; Garcia Masso, X.; Madera, J. (Biomechanics and Medicine in Swimming XI, 2010)
The main aim of this study was to examine whether there are differences in the LA accumulation in disabled swimmers belonging to the lower classes, higher classes and those without functional disability. The sample was made up of 38 swimmers, 10 disabled swimmers from classes 1 to 5 (G1), 9 swimmers from classes 6 to 10 (G2) and 10 swimmers without functional disability (G3). The swimmers performed two bouts of swimming: one anaerobic and the other aerobic-anaerobic. The Anova showed significant differences between the groups (p<0.005). Finally, in anaerobic and aerobic-anaerobic intensities, the swimmers of the lower classes have a lower LA accumulation than the swimmers from higher classes and the swimmers without any functional impairment.